Longitudinal evaluation of a hearing protector fit training program - Assunção, Caio Henrique de Carvalho; Trabanco, Júlio César; Gomes, Raquel Fornaziero; Moreira, Renata Rodrigues; Samelli, Alessandra Giannella (La Medicina del Lavoro, 2019)
Objective: The present study evaluates a training program for fitting different hearing protection devices (HPDs) based on personal attenuation rating (PAR) before, immediately after, and six months after training. Methods: A total of 67 workers from a public university in the city of São Paulo, Brazil, were invited to participate in the measurement of PARs for foam and silicone protectors through the 3M™ E-A-Rfit Validation System. Two evaluations were performed for each protector at each sampling date: one after reading printed material (the package instructions) and another after being trained by an audiologist. The same procedures were repeated after six months. The final sample consisted of 30 individuals. ANOVA was used for statistical analysis. Results: Larger PAR values ​​were observed after training by the audiologist, and smaller values ​​were observed after six months. Then, after re-training, the values increased again. There were no statistically significant differences in PAR among the HPDs tested. Even after the two training sessions, 23 to 27% of the subjects did not obtain adequate PAR values. Conclusion: These findings emphasize the need for continual worker training in the correct fit of earplug HPDs and the importance of longitudinal PAR monitoring. In addition, some workers, despite the training provided, did not adapt to the HPDs used. Therefore, it is essential that other protection methods and/or other HPD types are made available to these individuals.